1991
DOI: 10.1088/0031-8949/44/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Formal approach to the solution of the complex-spectra identification problem. I. theory

Abstract: A formal approach to the solution of the complex-spectra identification problem is proposed. In the frame of this approach the set of energy levels and transitions to be searched for is represented in the space of upper and lower energy levels as a geometric figure. The approach is based on the analysis of properties of two graphs which are the figure projections on the spaces of upper and lower energy levels. The methods for finding the original figure (or its versions) are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…Several groups have thus been recently making efforts to solve this lack. For example, Ryabtsev and co-workers [6][7][8] observed EUV spectra of W VIII excited in vacuum spark and made detail analysis of the spectra with the aid of a line identification program [9,10]. Through their efforts, it has been confirmed that the ground state configuration of W VIII is 4f 13 5s 2 5p 6 , which had been uncertain in the previous experimental [11] and theoretical [12,13] studies due to the competition with 4f 14 5s 2 5p 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have thus been recently making efforts to solve this lack. For example, Ryabtsev and co-workers [6][7][8] observed EUV spectra of W VIII excited in vacuum spark and made detail analysis of the spectra with the aid of a line identification program [9,10]. Through their efforts, it has been confirmed that the ground state configuration of W VIII is 4f 13 5s 2 5p 6 , which had been uncertain in the previous experimental [11] and theoretical [12,13] studies due to the competition with 4f 14 5s 2 5p 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of such combinations were found, which gave additional support for some identifications that Martin and Zalubas [ 121 had considered as being questionable. With the help of a special computer program for visualization of the spectrum identification process (designed by Azarov [25,26]), it was possible to re-assign many of those "questionable" transitions and to make the educated guess that some of them are masked by lines of either the carbon ions (in Hoory's spectra) or of other ionic species of Si. This work also revealed many gaps in the published line lists, and because of these gaps many questions still remain unresolved.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Immediately it became obvious that some of the data compiled by Kelly were not consistent. With the help of various techniques and computer programs designed at LAS [25,, it was found to be possible to make reassignments of many transitions, to find many new transitions and energy levels and to correct some misidentifications.…”
Section: Introductionmentioning
confidence: 99%
“…The IDEN computer program [15,16] employs an iterative level optimization procedure (LOP) [17] to optimize the energy level system. The reliability and accuracy of each established level is verified by the calculation of two types of uncertainties of the level with respect to the levels directly connected to it by the identified transitions.…”
Section: Level Optimization and Reliability Checkmentioning
confidence: 99%
“…The ion has the 5d 4 ground-state configuration. The current analysis is essentially based on theoretical calculations utilizing the orthogonal operators approach [11][12][13][14] and the program suite IDEN [15][16][17].…”
Section: Introduction and Experimentsmentioning
confidence: 99%